Genotyping and virological characteristics of hepatitis B virus in HIV-infected individuals in Sudan - Mukhlid Yousif; Hatim Mudawi; Waleed Hussein; Maowia Mukhtar; Omer Nemeri; Dieter Glebe; Anna Kramvis (International Journal of Infectious Diseases, 2014)
Objectives: Hepatitis B virus (HBV) and human immunodeficiency virus (HIV) share common routes of blood-borne transmission. In HBV mono-infected Sudanese individuals, genotypes D, E, and A circulate. The objective of this study was to molecularly characterize HBV from HBV/HIV co-infected individuals. Methods: The polymerase overlapping the S region and the basic core promoter (BCP/PC) of HBV from 32 hepatitis B surface antigen (HBsAg)-positive and 18 HBsAg-negative serum samples were amplified and sequenced. Results: HBV from 37 samples was successfully genotyped and the genotype distribution was 46.0% D, 21.6% E, 18.9% A, and 13.5% D/E recombinant. Compared to mono-infected individuals, the frequencies of the D/E recombinant and genotype A were higher in HBV/HIV co-infected patients, as was the intra-group divergence of genotype E. BCP/PC mutations affecting hepatitis B e antigen (HBeAg) expression at the transcriptional and translational levels were detected. Two HBsAg-positive individuals had pre-S deletion mutants. The following mutations in the S region could account for the HBsAg negativity: sM133T, sE164G, sV168G, and sS174N. No primary drug resistance mutations were found. Conclusions: In HBV/HIV co-infected Sudanese patients, the ratio of genotype A to non-A was higher than that in mono-infected patients. The genotype E intra-group divergence in HBV/HIV co-infected individuals was significantly higher than that in HBV mono-infected patients.